A prospective longitudinal study shows putamen volume is associated with moderate amphetamine use and resultant cognitive impairments. Issue 1 (18th March 2021) - Kendrick, Keith M; Daumann, Joerg; Wagner, Daniel; Koester, Philip; Tittgemeyer, Marc; Luo, Qiang; Gouzoulis-Mayfrank, Euphrosyne; Becker, Benjamin
Abstract: Background: Amphetamine-type stimulants (ATS) have become a critical public health issue. Animal models have indicated a clear neurotoxic potential of ATSs. In humans, chronic use has been associated with cognitive deficits and structural brain abnormalities. However, cross-sectional retrospective designs in chronic users cannot truly determine the causal direction of the effects. Objective: To prospectively determine effects of occasional ATS use on cognitive functioning and brain structure. Methods: In a prospective longitudinal study design, cognitive functioning and brain structure were assessed at baseline and at 12-month follow-up in occasional ATS users (cumulative lifetime use <10 units at baseline). Results: Examination of change scores between the initial examination and follow-up revealed declined verbal memory performance and putamen volume in users with high relative to low interim ATS exposure. In the entire sample, interim ATS use, memory decline, and putamen volume reductions were strongly associated. Conclusions: The present findings support the hypothesis that ATS use is associated with deficient dorsal striatal morphology that might reflect alterations in dopaminergic pathways. More importantly, these findings strongly suggest that even occasional, low-dose ATS use disrupts striatal integrity and cognitive functioning.